Potentials of MicroRNA in Early Detection of Ovarian Cancer by Analytical Electrical Biosensors. (3rd October 2022) - Parmin, N. A.; Hashim, Uda; Gopinath, Subash C. B.; Nadzirah, Sh.; Salimi, M.N.; Voon, C. H.; Uda, M. N. A.; Uda, M.N. Afnan; Rozi, Siti Khalijah Mahmad; Rejali, Zulida; Afzan, Amilia; Azan, Mohammad Isa Ahmad; et al.
Abstract: The importance of nanotechnology in medical applications especially with biomedical sensing devices is undoubted. Several medical diagnostics have been developed by taking the advantage of nanomaterials, especially with electrical biosensors. Biosensors have been predominantly used for the quantification of different clinical biomarkers toward detection, screening, and follow-up the treatment. At present, ovarian cancer is one of the severe complications that cannot be identified until it becomes most dangerous as the advanced stage. Based on the American Cancer Society, 20% of cases involved in the detection of ovarian cancer are diagnosed at an early stage and 80% diagnosed at the later stages. The patient just has a common digestive problem and stomach ache as early symptoms and people used to ignore these symptoms. Micro ribonucleic acid (miRNA) is classified as small non-coding RNAs, their expressions change due to the association of cancer development and progression. This article reviews and discusses on the currently available strategies for the early detection of ovarian cancers using miRNA as a biomarker associated with electrical biosensors. A unique miRNA-based biomarker detections are specially highlighted with biosensor platforms to diagnose ovarian cancer.